2019
DOI: 10.1186/s12864-019-5693-2
|View full text |Cite
|
Sign up to set email alerts
|

A high-density genetic map developed by specific-locus amplified fragment (SLAF) sequencing and identification of a locus controlling anthocyanin pigmentation in stalk of Zicaitai (Brassica rapa L. ssp. chinensis var. purpurea)

Abstract: Background: Caixin and Zicaitai (Brassica rapa) belong to Southern and Central China respectively. Zicaitai contains high amount of anthocyanin in leaf and stalk resulting to the purple color. Stalk is the major edible part and stalk color is an economically important trait for the two vegetables. The aim of this study is to construct a high density genetic map using the specific length amplified fragment sequencing (SLAF-seq) technique to explore genetic basis for anthocyanin pigmentation traits via quantitat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
27
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 66 publications
0
27
0
2
Order By: Relevance
“…chinensis var. purpurea), BrbHLH49, BrEGL3.2 and BrMYBL2.1 [19][20][21] ; purple bok choy (B. rapa L. ssp. chinensis), BrMYB73 22 ; purple tumorous stem mustard (Brassica juncea var.…”
Section: Introductionmentioning
confidence: 99%
“…chinensis var. purpurea), BrbHLH49, BrEGL3.2 and BrMYBL2.1 [19][20][21] ; purple bok choy (B. rapa L. ssp. chinensis), BrMYB73 22 ; purple tumorous stem mustard (Brassica juncea var.…”
Section: Introductionmentioning
confidence: 99%
“…BrMYB73 was predicted to encode a R2R3-MYB transcription factor, and one deletion and one SNP were found in this gene in purple-leaf parent. Recently, Li et al identified a bHLH49 transcription factor (BrbHLH49) on A07 that might positively regulate the anthocyanin accumulation in Zicaitai based on a specific-locus amplified fragment sequencing method 19 . These studies revealed the genetic diversity of anthocyanin biosynthesis related genes in Brassica crops.…”
Section: Discussionmentioning
confidence: 99%
“…The purple pigment of Zicaitai has been confirmed as anthocyanins 4 . Although several studies have characterized anthocyanins in Brassica crops [16][17][18][19] , there is limited information on the genes involved in anthocyanin biosynthesis in Zicaitai.…”
mentioning
confidence: 99%
“…Благодаря высокому содержанию уникальных биологически активных соединений в съедобных стеблях и листьях пурпурная капуста пользуется спросом в странах Азии, Европы и Америки (Li et al, 2019). В последние годы эта культура стала востребованным объектом для молекулярных и генетических исследований.…”
Section: Introductionunclassified
“…Такие исследования начаты и в отношении культуры B. purpuraria (Guo et al, 2015). Ведутся работы по созданию генетической карты для идентификации локусов контролирующих накопление антоциана в стебле растения (Li et al, 2019).…”
Section: Introductionunclassified